Cephalon, Inc. Taking risk management theory seriously - Chacko, George; Tufano, Peter; Verter, Geoffrey (Journal of Financial Economics, 2001)
Cephalon Inc., a biotech firm, bought call options on its own stock to meet its conditional cash flow needs. We analyze this decision by using the cash flow hedging concepts of Froot et al., (1993. Journal of Finance 5, 1629–1658). We identify the managerial analyses necessary to apply this theory and discuss managerial considerations absent from the theory. We find that managers consider deadweight costs of risk management, which theory tends to ignore. Theory provides little guidance in how to measure these and other deadweight costs. Finally, uncertainty about the availability of external financing and accounting considerations are critical considerations by managers.